CRYPTOCOCCOSIS IN ADVANCE STATE OF AIDS AND ITS CHALLENGING THERAPEUTIC REGIMEN: IS IT REALLY CURABLE? - Bhattacharya, Swetasri; Banerjee, Anindya (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Cryptococcosis followed by Cryptococcal meningitis (CM) is a deadly disease in an immuno-compromised patient with the complication of advance human immunodeficiency virus/AIDS, which comes through an air born virus Cryptococcus neoformans, from bird dropping. Immune reconstitution inflammatory syndrome is also often associated with this disease. A 10 years study showed a 17% prevalence of CM in a tertiary care hospital, among which 53.1% were infected with AIDS. Treatment guideline is amphotericin B (AmB) and 5-flucytosine or AmB and fluconazole, but the iatrogenic effect, cost and scarcity of availability of these drugs are the leading cause of mortality due to this disease. Anyhow, various novel therapeutic approaches have been taken to reduce and/or to prevent the pathogenesis of CM for the sake of mankind. Keywords: Antiretroviral therapy, Seizures, Hypokalemia, Hypomagnisemia.